Eccentric strength and endurance in patients with unilateral intermittent claudication - Márcio Basyches (Clinics, 2009)
OBJECTIVE: To analyze concentric and eccentric strength and endurance in patients with unilateral intermittent claudication. INTRODUCTION: Basic motor tasks are composed of concentric, isometric, and eccentric actions, which are related and contribute to physical performance. In previous studies of patients with intermittent claudication, the disease-related reduction in concentric and isometric muscular strength and endurance resulted in poorer walking performance. To date, no study has evaluated eccentric muscle action in patients with intermittent claudication. METHODS: Eleven patients with unilateral intermittent claudication performed isokinetic concentric and eccentric actions at the ankle joints to assess peak torque and total work in both symptomatic and asymptomatic legs. RESULTS: Concentric peak torque and total work were lower in the symptomatic than in the asymptomatic leg (80 ± 32 vs. 95 ± 41 N/m, P = 0.01; 1479 ± 667 vs. 1709 ± 879 J, P = 0.03, respectively). There were no differences in eccentric peak torque and total work between symptomatic and asymptomatic legs (96 ± 30 vs. 108 ± 48 N/m; 1852 ± 879 vs. 1891 ± 755 J, respectively). CONCLUSION: Strength and endurance in the symptomatic leg were lower during concentric compared to eccentric action. Future studies are recommended to investigate the mechanisms underlying these responses and to analyze the effects of interventions to improve concentric strength and endurance on functional limitations in patients with intermittent claudication.